Vocational School Entrepreneurship: The Role Of Teacher Innovativeness And Community Culture Through Digital Intelligence - Murison; Said, Mukti; Argunaini, Sri; Fauzan; Jailani, Syahran (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
School entrepreneurship has become a strategic indicator of vocational education performance in responding to global economic changes driven by digitalization, technological innovation, and the growth of the creative economy. Vocational High Schools (SMKs) are no longer expected merely to produce job-ready graduates, but also to develop institutional entrepreneurial capacity that is innovative, adaptive, and sustainable. A quantitative approach was employed using an explanatory research design. Data were collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results of the literature review and conceptual synthesis indicate that teacher innovativeness plays a critical role in driving entrepreneurship-oriented learning, while community culture shapes the social ecosystem that supports the sustainability of school entrepreneurship. These effects become more substantial when mediated by digital intelligence, which enables the transformation of pedagogical innovation and cultural values into technology-based entrepreneurial practices. This article contributes theoretically by strengthening a digital mediation-based model of school entrepreneurship and provides practical implications for vocational school management and policy development within the perspective of Islamic Education Management.